Antibacterial Efficacy and Drug-Induced Tooth Discolouration of Antibiotic Combinations for Endodontic Regenerative Procedures. (April 2013) - Mandras, N.; Roana, J.; Allizond, V.; Pasqualini, D.; Crosasso, P.; Burlando, M.; Banche, G.; Denisova, T.; Berutti, E.; Cuffini, A.M.
Elimination of microbial contamination from the root canal system is a precondition for successful root canal treatment. Teeth with immature root development, necrotic pulps and apical periodontitis present multiple challenges for successful treatment. Disinfection is achieved by irrigation followed by the placement of an intracanal medicament. A mixture of ciprofloxacin, metronidazole and minocycline (3-MIX S) has been shown to be very effective in eliminating endodontic pathogens in vitro and in vivo . Among the components of the mixture, minocycline can induce tooth discolouration after long-term oral use. Therefore, the elimination of minocycline from the above-mentioned combination has been suggested to prevent the occasion of this undesirable effect. The aim of this study was to investigate the potential antimicrobial efficacy of alternative antibiotic combinations [3-MIX C (clarithromycin); 3-MIX F (fosfomycin)] against bacteria from infected root canals. An additional objective was to evaluate their discolouration potential as possible alternatives to minocycline-based intracanal medicaments. Our in vitro results clearly demonstrated that 3-MIX C and 3-MIX F had a greater antimicrobial activity than 3-MIX S, underlying that clarithromycin still had a higher capacity to kill endodontic pathogens in vitro compared to fosfomycin. Both 3-MIX C and 3-MIX F were able to avoid the permanent staining effect of the crown.